Pertanggungjawaban Pidana Pelaku Peredaran Alat Rapid Test Sebagai Alat Kesehatan Tanpa Izin Edar - Nabilah Khansa Aribah Milansari (Faculty of Law, Universitas Airlangga, 2022)
AbstractIn the health sector, pharmaceutical preparations and medical devices that will be circulated to the public as well as the authorities in the use of these devices must be guaranteed safety in order to ensure that the pharmaceutical preparations and medical devices do not endanger the users. However, in practice legal problems arise where there is a circulation of rapid test equipment that does not have a distribution permit. The purpose of this study was to find out whether the act of distributing rapid test equipment without a distribution permit is a criminal act and what form of criminal responsibility for the perpetrators of the circulation of rapid test equipment without a distribution permit is formed. From the conceptual approach and the statutory approach taken, it was concluded that the act of distributing rapid test equipment without a distribution permit violates Article 60 of Law Number 11 of 2020 concerning Job Creation. Then for the accountability of the perpetrators of the circulation of rapid test equipment without a distribution permit, sanctions can be imposed in accordance with Article 197 of the Health Law and Article 62 of the Consumer Protection Act.Keywords: Criminal Liability; Rapid Test Tool; Circulation Permit. AbstrakDalam bidang kesehatan sediaan farmasi dan alat kesehatan yang akan diedarkan kepada masyarakat maupun pihak yang berwenang dalam penggunaan alat tersebut harus terjamin keamanannya guna memastikan bahwa sediaan farmasi maupun alat kesehatan tersebut tidak membahayakan penggunanya. Namun dalam praktiknya timbul permasalahan hukum dimana terdapat peredaran alat rapid test yang tidak memiliki izin edar. Tujuan penelitian ini adalah untuk mengetahui apakah perbuatan mengedarkan alat rapid test tanpa izin edar merupakan suatu tindak pidana dan bagaimana bentuk pertanggungjawaban piadna pelaku peredaran alat rapid test yang tidak memiliki izin edar tersebut. Dari pendekatan konseptual dan pendekatan perundang-undangan yang dilakukan, ditarik kesimpulan bahwa perbuatan mengedarkan alat rapid test tanpa izin edar melanggar Pasal 60 Undang-Undang Nomor 11 Tahun 2020 tentang Cipta Kerja. Kemudian untuk pertanggungjawaban pelaku peredaran alat rapid test tanpa izin edar tersebut dapat dikenakan sanksi sesuai pada pasal 197 Undang-Undang Kesehatan serta Pasal 62 Undang-Undang Perlindungan Konsumen.Kata Kunci: Pertanggungjawaban Pidana; Alat Rapid Test; Izin Edar.